Establishment of an in vitro mass propagation system for dendrocalamus asper - Anis Adilah Mustafa; Thau, Wilson Lym Yong; Julius Kulip; Kenneth Francis Rodrigues (Universiti Malaysia Sabah, 2023)
Dendrocalamus asper is a species of bamboo that has high commercial value and is the bamboo of choice for large scale agro-forestry plantations in the tropical regions of the world. Micropropagation using tissue culture is essential to generate uniform clones that are amenable to establishment in industrial agro-forestry projects for bamboo biomass, habitat restoration or in carbon sequestration. This paper reports on the establishment of D. asper invitro using commercially available seeds. The seeds were surface sterilized using three different chemical agents which were Sodium Hypochlorite (20%), Mercuric Chloride (0.1%) and Ethanol (70%) followed by shoot initiation on Murashige and Skoog (MS) medium supplemented with 6- Benzylaminopurine (BAP) with a concentration ranging from 1.0 - 5.0 mg/L. Propagules were multiplied on MS media supplemented with different concentration of IBA Indole-3-Butyric Acid (IBA) and Naphthalene Acetic Acid (NAA), and finally rooted and hardened in peat moss. The findings of our study indicate that the sterilization protocol eliminated all the plant pathogens, resulting in an axenic culture. Full strength MS medium supplemented with 5 mg/L BAP yielded the highest number of shoots (11.46 per explant) after four weeks of inoculation. The highest multiplication rate (3.95 shoots per explant) was obtained on MS medium supplemented with 3 mg/L BAP. The time required from initiation to hardening was 70 to 90 days, following which the plantlets were ready for field trials. The findings of this study will facilitate the establishment of plant tissue culture programmes dedicated to the production of D. asper locally, thus eliminating the need for imports and the possible entry of plant pathogens that can be detrimental to the local agroforestry industry.